Hot Topics in Infection and Immunity in Children IV - Finn, Adam; Pollard, Andrew J. (Advances in Experimental Medicine and Biology, 2008)
Hot Topics in Infection and Immunity in Children IV contains chapters based on lectures given by speakers at the "Infection and Immunity in Children" course, held in June 2006 at Keble College, Oxford. It was the fourth annual course of this name and this is the fourth book in the series as well. Together the courses and books have become important components of the training available to paediatricians with an interest in this specialty and have become increasingly popular each year. This book covers topics in infectious diseases in children and is intended for Pediatric Infectious Disease trainees, trainers, and all those who manage children with infections. Paediatric Infectious Diseases is now a recognised specialty in Europe with established training programmes and training centres, overseen by the European Society for Paediatric Infectious Diseases. This book and the course that precedes each edition will continue to play useful parts in the development and knowledge of specialists throughout the continent and beyond.